ANALISIS STRATEGI PEMASARAN DALAM UPAYA MENINGKATKAN MINAT BELI - Bobi, Yopinus; Sore, Avelius Dominggus; Tiara, Tiara (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
Marketing strategy is an effort to market a product or service, using a certain pattern of plans and tactics so that the number of sales becomes higher. Nowadays everything becomes easier including marketing strategies and this is in line with the development of the times, many shops have sold and promoted their products online and also sold products offline. So, it should be that shops in the city of Sintang can follow the current trends or developments. The purpose of this study is to see the marketing strategy that is suitable for increasing consumer buying interest. The method used in this study is a descriptive qualitative method with a descriptive research form. The data sources for this study are shop owners, employees and consumers. Data collection tools use observation, interview and documentation guidelines. The results of this study indicate that (1) marketing strategies can be implemented well with direct selling, upselling and cross-selling marketing strategies. (2) The strengths of the store are direct marketing strategies and promotions, (3) Cosmetic stores also have weaknesses, namely in transportation and employees who are still less confident and marketing locations that are far from the location, and (4) have threats such as competitors who use the same marketing strategy and shops in urban areas that use online platforms.